The Effects of Exposure to Repeated Minor Pain During the Neonatal Period on Formalin Pain Behavior and Thermal Withdrawal Latencies - C Celeste Johnston; Claire-Dominique Walker (Pain Research and Management)
Preterm infants undergoing untreated, repeated painful procedures as part of their early experience are more likely to behave differently to pain as they mature than infants who were born at term and did not experience excessive exogenous pain. The neonatal rat model was used to investigate the short- and long-term effects of repeated pain in infancy on later development of pain responses. Newborn rat pups were randomly assigned by litter to be left unhandled (UH), handled by being removed from the dam for 15 min four times daily (H), and being handled and receiving pain from a paw prick with a 26G needle four times daily (P)on postnatal days (PD) 2 through 8 (PD2-PD8). Maternal behaviour and grooming of pups on their return to the nest were recorded at PD6 for H and P pups. At PD15, PD36 and PD65, animals were first tested for latency to thermal stimulation threshold using the Hargreaves test and then for inflammatory pain using the formalin test. Pups in the HP group received significantly more grooming from their mothers (359 s) than pups in the H group (295 s, P<0.0001). When accounting for differences in maternal grooming, a decreased thermal threshold in the P group compared with the H group (6.04 s versus 5.3 s, P<0.05) was found, although the correlations were not significant between maternal grooming and thermal thresholds. No group differences were seen with the formalin test. Interestingly, age was a significant factor in both tests, with younger animals showing fewer pain behaviours regardless of group or maternal grooming of the pup. Sex was significant at one age only in latency to thermal stimulation testing. The results suggest that changes in maternal care may be an important factor mediating the long-term effects of repeated neonatal experiences of pain.